ANALISIS PERANGKAT PEMBELAJARAN MEMBACA PEMAHAMAN (PEMBELAJARAN TEMATIK DI KELAS IV SEKOLAH DASAR NEGERI 14 PONTIANAK UTARA) - Fitriani Fitriani; Siti Halidjah; Kartono Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract This study aims was to describe "Analysis of Learning Tools for Reading Comprehension (Thematic Learning in Grade IV of Public Elementary School 14 North Pontianak). The method used in this research was descriptive method, the type of research used was qualitative. Sources of data in this study were documents of reading comprehension learning tools in thematic learning compiled by grade IV teachers. The result show that there are components of the RPP that are appropriate and not in accordance with Permendikbud Number 22 of 2016 concerning process standars. The components that are suitable basic competencies, learning, resources, learning materials. While the unsuitable part are the indicators of competency achievement, writing of the five lesson plans analyzed, the percentage of conformity between the lesson planst amd the standar process was that RPP 1 reached 74,2%, RPP 2 reached 77,1%, RPP 3 reached 80%, RPP 4 and RPP 5 reached 82,8%. Furthermore, when viewed from the data on the completeness of teaching materials, there are only two lesson plans whose teaching material is 100% in accordance with the reading comprehension steps. Namely in RPP 4 and 5, while for RPP 1 it was 80%, RPP 2 was 40%, RPP 3 was 60%. Keywords: Analysis, LearningTools, Reading Comprehension,Thematic Learning